A basal heat stress test to detect military operational readiness after a 14-day operational heat acclimatization period. Issue 3 (2nd July 2020) - Malgoyre, Alexandra; Siracusa, Julien; Tardo-Dino, Pierre-Emmanuel; Garcia-Vicencio, Sebastian; Koulmann, Nathalie; Charlot, Keyne
ABSTRACT: A basal heat stress test (HST) to predict the magnitude of adaptive responses during heat acclimatization (HA) would be highly useful for the armed forces. The aim was to identify physiological markers assessed during a HST (three 8-min running sets at 50% of the speed at VO2max ) performed just before a 14-day HA period that would identify participants still at "risk" at the end of HA. Individuals that responded poorly (large increases in rectal temperature [Trec ] and heart rate [HR]) during the initial HST were more likely to respond favorably to HA (large reductions in Trec and HR). However, they were also more likely to exhibit lower tolerance to HST at D15. Basal Trec was found to efficiently discriminate participants showing a Trec > 38.5°C after HA, who are considered to be "at risk". Finally, participants were classified by quartiles based on basal Trec and HR at the end of the HST and physiological strain index (PSI). Most of the participants "at risk" were among the upper quartile (i.e. the least tolerant) of Trec and PSI ( p = 0.011 for both). Overall, these results show that the individuals who are less tolerant to a basal HST are very likely to benefit the most from HA but they also remain less tolerant to heat at the end of HA than those who better tolerated the basal HST. A basal HST could therefore theoretically help the command to select the most-ready personnel in hot conditions while retaining those who are less tolerant 6 .